2008
DOI: 10.1177/154193120805201503
|View full text |Cite
|
Sign up to set email alerts
|

Where and How College Students Use Their Laptop Computers

Abstract: A pilot study classified the locations, furniture, input devices and postures associated with using laptop computers in a small cohort of college students. Data were collected from digital photographs of the students posing as using laptop computers in their usual workstation configurations. The observed configurations were assigned to descriptive categories and the Rapid Upper Limb Assessment (RULA) assessed the postural risk factors observed on the participants. We observed that 75% of the participants used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…In partial agreement with findings by Chang, Amick, Menendez, Robertson and del Pino and Dennerlein 18 who indicate that all college students' (n=54) RULA scores during the use of a laptop in different positions ranged between two (negligible risk) to four (low risk), results from the current study indicated that most participants fell within the low risk postural category. The difference in results is that in the current study five out of 72 participants scored in the medium risk category and one participant scored in the very high risk category.…”
Section: Discussionsupporting
confidence: 80%
“…In partial agreement with findings by Chang, Amick, Menendez, Robertson and del Pino and Dennerlein 18 who indicate that all college students' (n=54) RULA scores during the use of a laptop in different positions ranged between two (negligible risk) to four (low risk), results from the current study indicated that most participants fell within the low risk postural category. The difference in results is that in the current study five out of 72 participants scored in the medium risk category and one participant scored in the very high risk category.…”
Section: Discussionsupporting
confidence: 80%
“…Results from this study confirm findings by Chang et al 4 , De Beer 22 and Bowman et al 3 that indicate laptops to be the preferred technological device for educational purposes amongst university students. (see Table 1).…”
Section: Discussionsupporting
confidence: 82%
“…In a study amongst 154 college students, Chang and colleagues found that 88% of the population in the United States of America owned a laptop and that a growing number of students prefer to make use of laptop computers instead of desktop computers 4 . .…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al (2008) found that up to 88% of college students own a laptop computer, with 82% using a laptop exclusively over a desktop. Laptop computers are ideal for student use because of their small size and portability.…”
Section: Risk Factors Associated With Laptop Computer Usementioning
confidence: 99%
“…In a pilot study aimed at identifying and examining popular workstation configurations utilized by college students, Chang et al (2008) performed a postural analysis on photographs of students using laptop computers in various self-selected set ups including: sitting at a table in a chair, sitting on a bed with a laptop on the lap, lying on a bed with a laptop on the bed, sitting on a chair with a laptop on the lap, and sitting on a lounge-style couch with a laptop on the lap. The The additional body positions that were analyzed in this study were the three most frequently identified positions by the participants.…”
Section: Laptop Use In Alternative Configurationsmentioning
confidence: 99%